Supplementary Information Files for "Microencapsulation of Salmonella-Specific Bacteriophage Felix O1 Using Spray-Drying in a pH-Responsive Formulation and Direct Compression Tableting of Powders into a Solid Oral Dosage Form" - Gurinder Vinner; Zahra Rezaie-Yazdi; Miika Leppanen; Andrew G. F. Stapley; Mark Leaper; Danish Malik (2019)
Supplementary Information Files for "Microencapsulation of Salmonella-Specific Bacteriophage Felix O1 Using Spray-Drying in a pH-Responsive Formulation and Direct Compression Tableting of Powders into a Solid Oral Dosage Form"Abstract:The treatment of enteric bacterial infections using oral bacteriophage therapy can be challenging since the harsh acidic stomach environment renders phages inactive during transit through the gastrointestinal tract. Solid oral dosage forms allowing site-specific gastrointestinal delivery of high doses of phages, e.g., using a pH or enzymatic trigger, would be a game changer for the nascent industry trying to demonstrate the efficacy of phages, including engineered phages for gut microbiome modulation in expensive clinical trials. Spray-drying is a scalable, low-cost process for producing pharmaceutical agents in dry powder form. Encapsulation of a model Salmonella-specific phage (Myoviridae phage Felix O1) was carried out using the process of spray-drying, employing a commercially available Eudragit S100® pH-responsive anionic copolymer composed of methyl methacrylate-co-methacrylic acid formulated with trehalose. Formulation and processing conditions were optimised to improve the survival of phages during spray-drying, and their subsequent protection upon exposure to simulated gastric acidity was demonstrated. Addition of trehalose to the formulation was shown to protect phages from elevated temperatures and desiccation encountered during spray-drying. Direct compression of spray-dried encapsulated phages into tablets was shown to significantly improve phage protection upon exposure to simulated gastric fluid. The results reported here demonstrate the significant potential of spray-dried pH-responsive formulations for oral delivery of bacteriophages targeting gastrointestinal applications.